The Relevance of Gratitude in Self-Healing According to the Quran from the Perspective of M. Quraish Shihab - Putra , M. Rizky Adriansyah; Azmi, Ulul; Astuti, Rahayu Fuji (Pascasarjana Universitas Mataram, 2024)
This article explores the relationship between gratitude and self-healing. Self-healing is a psychological healing process that occurs in people suffering from depression, stress, anxiety, and fear in life. This research aims to understand the practice of gratitude in self-healing in the Quran from the perspective of M. Quraish Shihab. The results of this research regarding the interpretation of M. Quraish Shihab include verses of gratitude, namely Surah al-Baqarah verse 152, Surah 'Ali Imran verse 145, Surah Luqman verse 12, and Surah az-Zumar verse 7. Tafsir al-Misbah explains the words of gratitude as follows: This includes obedience and praise that deeply acknowledges the greatness of God's blessings and mercy and evokes feelings of love for God. Gratitude is closely related to maintaining mental health and peace of mind. Practicing self-healing with gratitude degrades negative thoughts, reduces feelings of dissatisfaction, fosters positive traits within oneself, and encourages a spirit of worship that provides psychological benefits. This occurs due to the increased awareness of Allah SWT's blessings in what is given in the lives of those who are grateful.